2021
DOI: 10.4103/jfmpc.jfmpc_2358_20
|View full text |Cite
|
Sign up to set email alerts
|

Safe and appropriate use of diclofenac in chronic kidney disease

Abstract: Pain is most common symptom associated with progressive disorder, chronic kidney disease (CKD), and is usually undertreated during the early stages of CKD. So, present review was conducted to evaluate the challenges for the management of pain in CKD patients and addresses the scope for considering Diclofenac as suitable alternative for pain management in CKD patient. The database PubMed and Google Scholar were searched from 1970 to Dec 2020 for literature published in English and all studies, review articles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…The notable acceptance of diclofenac can be attributed to being a potent COX-2 inhibitor while maintaining similar activity to some other popular non-selective NSAIDs. Tests have shown that diclofenac inhibits COX-2 enzyme with higher potency than COX-1 [14]. Since specific and robust expressions of KCNQ2/3 channels in neurons and loss of function can lead to neuronal hyperexcitability, pharmacological activation of KCNQ2/3 channels is the basis of epilepsy and pain treatment [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The notable acceptance of diclofenac can be attributed to being a potent COX-2 inhibitor while maintaining similar activity to some other popular non-selective NSAIDs. Tests have shown that diclofenac inhibits COX-2 enzyme with higher potency than COX-1 [14]. Since specific and robust expressions of KCNQ2/3 channels in neurons and loss of function can lead to neuronal hyperexcitability, pharmacological activation of KCNQ2/3 channels is the basis of epilepsy and pain treatment [32].…”
Section: Discussionmentioning
confidence: 99%
“…Common mode of action for all NSAIDs is the inhibition of COX enzymes resulting in reduced prostanoid synthesis [13]. Diclofenac potassium is a compound with non-steroid anti-inflammatory, analgesic and antipyretic effects [14]. It is a benzene acetic acid derivative showing COX-2 enzyme inhibition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the prudent use of short plasma half-life NSAIDs may be taken into consideration, regular renal function monitoring is crucial. This is especially necessary if dialysis was not necessary prior to treatment [24][25][26]. Apart from renal considerations, diclofenac and ibuprofen increase the risk of severe coronary events.…”
Section: Key Pointsmentioning
confidence: 99%
“…Chronic kidney disease is a large group of diseases that have different causes but are united by the fact that they have a long course and a tendency to progress until complete loss of kidney function [5,6]. In renal pathology, one of the pathogenetic chains is associated with impaired calcium (hypo-or hypercalcaemia) and phosphorus (hyperphosphatemia) metabolism [7]. A deficiency of active vitamin D and impaired parathyroid hormone secretion (secondary or tertiary hyperparathyroidism) lead to bone metabolism disorders (renal osteodystrophy) and calcification of blood vessels and other soft tissues, accompanied by progressive bone structure disorders due to too fast (caused by hyperparathyroidism) or too slow (socalled adynamic bone disease) bone metabolism.…”
Section: стоматологія / Dentistry Connection Of the Publication With ...mentioning
confidence: 99%